2010
DOI: 10.1039/b918719g
|View full text |Cite
|
Sign up to set email alerts
|

Platelet retraction force measurements using flexible post force sensors

Abstract: Platelets play an important role in hemostasis by forming a thrombotic plug that seals the vessel wall and promotes vascular healing. After platelets adhere and aggregate at the wound site, their next step is to generate contractile forces through the coordination of physicochemical interactions between actin, myosin, and αIIbβ3 integrin receptors that retract the thrombus' size and strengthen its adhesion to the exposed matrix. Although platelet contractile forces (PCF) are a definitive feature of hemostasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 45 publications
5
88
1
Order By: Relevance
“…Consistent with the previous studies, 14,36 T101 inhibited HMW species formation at ;40-fold lower concentrations than it inhibited g-g dimer formation (IC 50 5 0.52 6 0.12 vs 21.1 6 5.8 mM, respectively, P , .03; Figure 7B). Importantly, when we superimposed the effects of T101 on fibrin crosslinking, clot weight, and RBC retention, we found that T101 reduced clot weight (IC 50 5 0.60 6 0.09 mM; Figure 7B) and RBC retention (data not shown) at the same concentrations at which it inhibited HMW species formation ( Figure 7B). Together, these data show FXIIIa promotes RBC retention in clots by crosslinking fibrin a-chains.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with the previous studies, 14,36 T101 inhibited HMW species formation at ;40-fold lower concentrations than it inhibited g-g dimer formation (IC 50 5 0.52 6 0.12 vs 21.1 6 5.8 mM, respectively, P , .03; Figure 7B). Importantly, when we superimposed the effects of T101 on fibrin crosslinking, clot weight, and RBC retention, we found that T101 reduced clot weight (IC 50 5 0.60 6 0.09 mM; Figure 7B) and RBC retention (data not shown) at the same concentrations at which it inhibited HMW species formation ( Figure 7B). Together, these data show FXIIIa promotes RBC retention in clots by crosslinking fibrin a-chains.…”
supporting
confidence: 79%
“…Clot contraction induces the appearance of compacted RBCs (so-called "polyhedrocytes"). 49 This observation demonstrates substantial platelet-mediated forces are transmitted through the clot during contraction 50,51 and suggests the fibrin network must be sufficiently dense and stiff to retain RBCs during this process. The contribution of crosslinking to fibrin elasticity, extensibility, and stiffness occurs at both whole-clot and single-fiber scales.…”
Section: Discussionmentioning
confidence: 99%
“…For example, rheology measurements on clot contraction yield a maximum contractile force per platelet of ,0.5 nN (Jen and McIntire, 1982). Even force measurements on smaller cell ensembles, namely microclots on elastic pillars, display contractile forces per platelet as low as 2.1 nN (Liang et al, 2010). This discrepancy is all the more striking, if we consider that the traction forces we measure with TFM are, if biased at all, an underestimate.…”
Section: Contractile Forces and Force Generating Mechanisms In Singlementioning
confidence: 71%
“…Furthermore, the experimental conditions are difficult to control as the samples contain blood plasma and hence several clotting agents; in both methods external forces are applied to the sample, which may influence clot formation. In a recent approach, Liang et al circumvented these problems by washing platelets in buffer prior to experiments and looking at contraction of microclots on a dense array of elastic microposts (Liang et al, 2010). They measured contractile forces per platelet of 2.1 nN 60 min after the initiation of clotting.…”
Section: Introductionmentioning
confidence: 99%
“…Force perturbations are created by cells as they push and pull on their immediate surroundings, be it neighboring cells or the extracellular matrix (ECM), as they change their morphology or orientation in response to external mechanical constraints and, of course, as they migrate and divide. The underlying basis of these diverse examples is the ability of essentially all cells, not just muscle cells, to generate and apply force (Discher et al, 2005;Harris et al, 1980;Liang et al, 2010) and, no less important, their capacity to sense 'informative mechanical cues' and develop a specific physiological (often biochemical) response.…”
Section: Introduction -Cellular Mechanosensitivity As An Emerging Parmentioning
confidence: 99%